Isomorphisms of matrix groups over commutative rings - Vasyl Petechuk; Julia Petechuk; Петечук Василь; Петечук Юлія; Petecsuk László; Petecsuk Júlia (Bolyai Institute, University of Szeged, 2017)
Abstract. We give a description of the isomorphism classes of matrix groups over commutative rings with 1 and that have dimension more than 3 and containing the group of elementary transvections. We characterize those homomorphisms of matrix groupe, which satisfy the so-called (*) condition. Such homomorphisms can be constructed with the help of the standard homomorphism. We apply the characterization obtained to the description of the above class of matrix groups.
http://pub.acta.hu/acta/showCustomerVolume.action?id=48928&dataObjectType=volume&noDataSet=true&style=
Keywords: linear group over ring; homomorphism of matrix group; elementary subgroup over ring